KAJIAN PENERAPAN KAMPUS RAMAH LINGKUNGAN (GREEN CAMPUS) DI STT MIGAS BALIKPAPAN - Risna Risna; Esterina Paindan; Eltimeyansi Crisye Randanan; Mohammad Lutfi (Sekolah Tinggi Teknologi MIGAS, 2021)
Global Warming is one of the environmental problems today. Efforts of anticipatons as a form of concern, have been carried out by various environmental movement programs, initiated by the government, NGOs and the community. In principle, environmentally friendly campus management is one of the determinants in producing the quality and quantity of the ongoing educational process. The purpose of this research is to study the application of an environmentally friendly campus using the fishbone diagram method to analyze the cause and effect of a problem. The results of the cause and effect analysis are then used as input to formulate internal factors in the SWOT, then produce strategies to minimize obstacles and increase the success of the green campus. This research is useful for educational institutions at STT Migas Balikpapan because it can provide an understanding of campus management policies that are oriented towards environmental management, in an effort to implement environmental education for students, as well as the care and involvement of all elements of the academic community in a culture of environmental care.